2019
DOI: 10.1186/s12913-019-4836-0
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a hospital transfusion management system promotes appropriate clinical use of human albumin in Japan: a nationwide retrospective study

Abstract: BackgroundDespite international recommendations to establish hospital transfusion management systems to promote appropriate use of blood products, the general efficacy of establishing such systems has not been proven. This study aimed to validate the effect of establishing such systems for promoting the appropriate use of human albumin.MethodsIn this retrospective observational study, we used a Japanese Diagnosis Procedure Combination (DPC) database from fiscal year 2012 to 2016, which included inpatient recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…There have not been any RCTs comparing the efficacy and safety of different concentrations of HSA solutions for fluid resuscitation in patients with sepsis. However, in published large-scale RCTs, low-(4% or 5%) and highconcentration (20% or 25%) HSA solutions have been used as resuscitation fluids, and no serious adverse events have been reported, [8][9][10][11][12][13][14][15][16] confirming that low-and highconcentration HSA solutions are safe in patients with sepsis. Different concentrations of HSA were used in different trials: 4% albumin was used in the SAFE and RASP trials, and 20% albumin was used in the ALBIOS trial.…”
Section: Development Process Of the Consensusmentioning
confidence: 99%
See 1 more Smart Citation
“…There have not been any RCTs comparing the efficacy and safety of different concentrations of HSA solutions for fluid resuscitation in patients with sepsis. However, in published large-scale RCTs, low-(4% or 5%) and highconcentration (20% or 25%) HSA solutions have been used as resuscitation fluids, and no serious adverse events have been reported, [8][9][10][11][12][13][14][15][16] confirming that low-and highconcentration HSA solutions are safe in patients with sepsis. Different concentrations of HSA were used in different trials: 4% albumin was used in the SAFE and RASP trials, and 20% albumin was used in the ALBIOS trial.…”
Section: Development Process Of the Consensusmentioning
confidence: 99%
“…In clinical practice, guidelines and consensus are lacking regarding the selection of HSA concentration, the timing of administration, dosage, and target concentration. Inappropriate use of HSA will cause adverse effects and increase medical costs inevitably, whereas guidance from clinical pharmacists or hospital standards can help reduce inappropriate HSA use by 30% and decrease medical costs without affecting patient prognosis [12] . To further strengthen the standardized application of HSA in critically ill patients and achieve optimal clinical outcomes, the Chinese Society of Critical Care Medicine convened a panel of relevant experts who reviewed and summarized data on the clinical use of HSA, outlined 11 relevant clinical problems, and formulated the “Expert Consensus on the Use of Human Serum Albumin in Critically Ill Patients” using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology.…”
Section: Introductionmentioning
confidence: 99%
“…introduction of a transfusion protocol, led to savings of economic resources without impairing the outcome. Transfusion protocols were implemented in 66% of the included hospitals [50]. Similar numbers are presented by a survey of the Japanese Ministry of Health on the use of blood products, which reported that 64% of all hospitals follow good practice criteria [51].…”
Section: Japanmentioning
confidence: 79%
“…According to a recent study using Japanese nationwide inpatient record data, patients admitted to hospitals with a transfusion management system, where the transfusion department stores and dispenses albumin and promotes appropriate albumin use, were less likely to receive albumin than patients admitted to hospitals without such a system. 17 However, the transfusion management system’s impact on albumin use in the ICU had not been elucidated. Our results indicate that albumin stock prohibition on the floor, rather than albumin management by the transfusion department per se , is the key driver in reducing albumin use.…”
Section: Discussionmentioning
confidence: 99%